Experimental Investigation of the Behaviour of Short-Span FRP-Reinforced Glulam Beams with Hoops and Tension Anchoring - Herry Chen; Yannick Vetter; Catherine Shrimpton; Daniel Lacroix (Fibers, 2025)
Past research has shown that for short-span glulam beams reinforced with a simple tension GFRP fabric can lead to undesirable failure modes at the reinforcement termination point. An experimental programme aimed at investigating alternative reinforcement schemes comprising hoops and tension anchoring as an alternative to fan-type anchorage and full-length confinement was undertaken. Sixteen GFRP-reinforced glulam beams were tested to failure under four-point bending. Overall, the hoops and tension anchoring prevented premature debonding and stress concentration failures observed in beams reinforced with simple tension reinforcement. Improvements in the stiffness and strength were generally observed for all configurations with the average failure strain being on average 1.16 times larger than the unreinforced specimens. While hoops prevented undesirable failure modes, it had limited improvements when using bidirectional fabrics for the hoops. Conversely, the configurations with tension anchoring using bidirectional fabrics only resulted in improved performance with some level of post-peak resistance compared to the unreinforced specimens and those reinforced with simple tension reinforcement. For short-span beams, or any FRP-reinforced glulam beams where flexure is not the dominant failure mode, more robust modelling techniques are required to properly capture the distribution of the reinforcement.